Structural characteristics of the N-glycans of two isoforms of prostate-specific antigens purified from human seminal fluid - Okada, Toyohiro; Sato, Yuji; Kobayashi, Norifumi; Sumida, Kyoichi; Satomura, Shinji; Matsuura, Shuji; Takasaki, Masaru; Endo, Tamao (Biochimica et biophysica acta, 2001)
Prostate-specific antigen (PSA) is a glycosylated chymotrypsin-like serine protease and is found mainly in prostatic tissue and seminal fluid. We purified two forms of PSA (PSA-A and PSA-B) from human seminal fluid with p I values of approx. 7.2 and approx. 6.9, respectively. To characterize the N-glycans of the two isoforms, the sugar chains were liberated by hydrazinolysis followed by N-acetylation, and derivatized with 2-aminobenzamide. Both PSA-A and PSA-B contained mono- and disialylated sugar chains, although PSA-B had a much higher content of the latter. After removal of sialic acid residues by sialidase digestion, mono- and biantennary N-glycans and three outer chain moieties (Galβ1-4GlcNAcβ1-, GlcNAcβ1-, GalNAcβ1-4GlcNAcβ1-) were found in both samples. However, the ratios of each N-glycan were different. These results indicate that PSA-A and PSA-B differ not only in their sialic acid contents, but also in their outer chain features.